2016
DOI: 10.1111/joim.12506
|View full text |Cite
|
Sign up to set email alerts
|

Current and future treatment of amyloid diseases

Abstract: There are more than 30 human proteins whose aggregation appears to cause degenerative maladies referred to as amyloid diseases or amyloidoses. These disorders are named after the characteristic cross-β-sheet amyloid fibrils that accumulate systemically or are localized to specific organs. In most cases current treatment is limited to symptomatic approaches and thus disease-modifying therapies are needed. Alzheimer’s disease is a neurodegenerative disorder with amyloid β-peptide (Aβ) plaques and tau neurofibril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 238 publications
0
73
0
1
Order By: Relevance
“…New drugs designed to kill non-growing bacteria (12861290) or to overcome amyloid coagulopathies (12911295) will be needed and will come to the fore.…”
Section: Other Predictionsmentioning
confidence: 99%
“…New drugs designed to kill non-growing bacteria (12861290) or to overcome amyloid coagulopathies (12911295) will be needed and will come to the fore.…”
Section: Other Predictionsmentioning
confidence: 99%
“…AD is an example of a localized cerebral amyloidosis and type 2 diabetes mellitus is an example of localized extracerebral amyloidosis; both diseases are associated with aging. (206) Transthyretin (TTR) (207), immunoglobulin light chain (LC) (208), serum amyloid A (SAA) (209), and Aβ (210) are examples of more than thirty human proteins whose misfolding and/or misassembly into a variety of aggregate structures appear to cause a spectrum of degenerative disorders (211). These so-called amyloid diseases are named after the cross-β-sheet aggregates, or amyloid fibrils, that are the pathological hallmarks of these maladies.…”
Section: Mitochondrial -Lysosomal Dysfunction In Nddmentioning
confidence: 99%
“…TTR suppressed Aβ and prevent its toxicity [89] [90]. Studies showed that TTR sequestered Aβ in the CSF and J. Iqbal Journal of Behavioral and Brain Science moved Aβ to the choroid plexus (CP) for enzymatic degradation and removal from the brain [18].…”
Section: Ttr Role In Alzheimer Diseasementioning
confidence: 99%